The Effectiveness of Interactive Learning Media Based On Articulate Storylines In Balaghah Learning - Marlion, Ferki Ahmad; Rasyid, Ifkar; Trisna, Destiva (Journal of Arabic Language Studies and Teaching, 2025)
This study aims to analyze in depth the effectiveness of Articulate Storylines as a learning medium for learning Ilmu Bayan in the Balaghah. This study uses a literature review method. The data analysis techniques employed in this study involve examining theories and ideas presented in the literature relevant to the research topic. Data collection in this study was conducted through various diverse literature sources, such as articles, journals, books, and research relevant to Articulate Storylines and Ilmu Bayan learning. Literature sources obtained from various references are analyzed carefully. These sources are selected to provide in-depth insights into the application of technology that can be used in language education, especially in increasing the effectiveness of Ilmu Bayan learning. Ilmu Bayan is one of the Balaghah branches that is often considered a branch with difficult material to understand, because the material of Ilmu Bayan contains kinayah, isti'arah, majaz, and tasybih, which are almost similar. Therefore, the use of Articulate Storylines media can be a solution to understanding and differentiating the materials in the study of Ilmu Bayan. It is because Articulate Storylines has highly effective features to support improved learning outcomes, not only making learning enjoyable but also enhancing the learning process to be innovative and effective.